Inhibition of Cor-Ten steel corrosion by "green" extracts of Brassica campestris. (15th May 2018) - Casaletto, Maria Pia; Figà, Viviana; Privitera, Antonella; Bruno, Maurizio; Napolitano, Assunta; Piacente, Sonia
Graphical abstract: Highlights: Brassica campestris extract was tested as ' green ' Cor-Ten steel corrosion inhibitor by electrochemical and surface techniques. NaCl and acidic solutions were the corrosive media for mimicking marine and urban polluted environments, respectively. Brassica campestris acts as an anodic inhibitor in NaCl solutions with the best inhibition efficiency (80–84%) for 80 ppm. In acidic solutions, a very weak inhibiting effect was found (IE ∼ 30% for 120 ppm). XPS surface analysis was used for interpreting the corrosive/inhibition phenomena. Abstract: Extract of Brassica campestris was tested as potential corrosion inhibitor for Cor-Ten steel in NaCl and acidic solutions, simulating a marine and an urban-industrial environment, respectively. Potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) were performed both in absence and in presence of the extract at room temperature. The surface chemical analysis was investigated by X-ray Photoemission Spectroscopy (XPS), before and after corrosion. Electrochemical results demonstrated that a very small concentration of Brassica campestris extracts can inhibit Cor-Ten corrosion in NaCl solution (inhibition efficiency of 80–84%) better than in acidic solutions. Surface analysis results confirmed these good results.